Ճարտարապետական ռեկրեացիոն ռեսուրսների դերը զբոսաշրջության մեջ - Գևորգ Գևորգյան; Արմինե Գուլոյան (ՀՀ ԳԱԱ հրատ.)
В статье пoказана роль архитектурных рекреационных реформ в организации туризма и их роль в социально-экономическом развитии республики. Рассматриваются проблемы, связанные с обслуживанием градостроительных и архитектурных памятников, связанных с реализацией данной роли. Приведены доводы о важности градостроительных и архитектурных мемориалов в деле развития туризма в Республике Армения. The article presents the role of architectural recreational reforms in the organization of tourism and their role in the socio-economic development of the republic. The problems connected with servicing of town-planning and architectural monuments connected with the realization of this role are considered. The arguments about the importance of town-planning and architectural memorials in the development of tourism of the Republic of Armenia are presented.
Keywords: Tourism; Architecture